Emergency treatment in Lombardy: a new methodology for the pre-Hospital Drugs management on Advanced Rescue Vehicles: Drugs management on Advanced Rescue Vehicles - Perego, Elisa; Balzarini, Federica; Botteri, Marco; Favetti, Stefania; Zoli, Alberto; Sechi, Giuseppe Maria; Odone, Anna; Signorelli, Carlo; Villa, Guido Francesco (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: The main objectives of our work were the regional harmonization and standardization of pharmaceutical supplies on MSA in Lombardy. Methods: The retrospective investigation was articulated in 2 phases: the first was the collection of data in every area of the Region (2012), the second was the analysis and elaboration of the information retrieved. Results: Beginning with 24 common drugs used by 8 AATs out of 12 an evaluation of the chemical-therapeutic characteristics was performed. The temporary list, including over 80 drugs classified in more than 25 therapeutic groups, was finally reduced to provide bags that were easier to handle but at the same time complete. Between October and November 2014, the proposed supply, including 71 formulations and approved by the Technical Board of AREU, officially entered into force. At the same time, the working group followed the same procedure to define the standard equipment for the Region’s helicopters, with only 58 formulations for relatively reduced weight allowed on board. Conclusions: In conclusion, we can state that, thanks to the support of experts, of the literature review, and thanks to the practical experience of the members of the AREU working groups and thanks to the documents coming from AIFA and EMA, the first operative regional project of unified pharmacological supply for MSA was delivered.